Magnetoplasmons in simple hexagonal graphite. Issue 66 (19th July 2015) - Chen, Rong-Bin; Chiu, Chih-Wei; Lin, Ming-Fa
<x xml:space="preserve">Abstract</x> Magneto-electronic Coulomb excitations in simple hexagonal graphite (SHG) are studied within the randomphase approximation.